Integration of Emerging Biomedical Technologies in Meat Processing to Improve Meat Safety and Quality - Ravensdale, Joshua; Coorey, Ranil; Dykes, Gary (Institute of Food Technologists, 2018)
© 2018 Institute of Food Technologists®. Modern-day processing of meat products involves a series of complex procedures designed to ensure the quality and safety of the meat for consumers. As the size of abattoirs increases, the logistical problems associated with large-capacity animal processing can affect the sanitation of the facility and the meat products, potentially increasing transmission of infectious diseases. Additionally, spoilage of food from improper processing and storage increases the global economic and ecological burden of meat production. Advances in biomedical and materials science have allowed for the development of innovative new antibacterial technologies that have broad applications in the medical industry. Additionally, new approaches in tissue engineering and nondestructive cooling of biological specimens could significantly improve organ transplantation and tissue grafting. These same strategies may be even more effective in the preservation and protection of meat as animal carcasses are easier to manipulate and do not have the same stringent requirements of care as living patients. This review presents potential applications of emerging biomedical technologies in the food industry to improve meat safety and quality. Future research directions investigating these new technologies and their usefulness in the meat processing chain along with regulatory, logistical, and consumer perception issues will also be discussed.